Heat generation in spatially confined solids through electronic light scattering - Kharintsev Sergey S.; Battalova Elina I. (Nanophotonics)
This study focuses on the optical heating of spatially dispersive solids due to electronic light scattering (ELS), a phenomenon driven by indirect optical transitions. In this process, a light-illuminated spatial heterogeneity generates an optical near-field photon with expanded momentum and thereby electron-photon momentum matching can be fulfilled. It results in indirect optical transitions which contribute to broadband inelastic emission, a physical process known as electronic light scattering or Compton scattering of visible photons. This is followed by thermalization of the electron system, making the solids to heat up and eventually melt. We experimentally demonstrate this effect by optical melting a spatially confined semiconductor (Si) and metal (Au) under moderate continuous-wave laser illumination with the intensity of only a few MW/cm2. We claim that ELS represents the dominant physical mechanism governing the interaction of light with spatially dispersive media, underpinning a broad range of thermo-optical phenomena and applications.